The differential effects of dynamic, static, and combined activities in forest bathing on health outcomes by gender in older adults: evidence from a national forest park trial - Yin, Menglei; Xu, Zhiman; Zheng, Xiaojun; Jiao, Rui; Li, Kankan (Frontiers in Psychology, 2025)
BackgroundForest bathing, as a form of natural therapy, has been increasingly recognized for its therapeutic effects on physiological and psychological health. National parks, as protected natural environments, provide ideal settings for such interventions, yet empirical studies conducted directly within these landscapes remain limited.ObjectiveThis study aims to compare the effects of dynamic, static, and combined dynamic-static activities on the health outcomes of older adult populations of different genders, within a real national park environment.MethodsSeventy-two middle-aged and older adults (mean age 62.5 ± 7.22 years) were divided into four groups: combined dynamic-static, dynamic, static, and control. Physiological (EEG, HR, skin conductance, SBP, DBP) and psychological indicators (BPOMS, PRS) were measured.ResultsThe combined dynamic-static group showed the best overall improvements, particularly in positive emotions and blood pressure. The dynamic group excelled in diastolic pressure and perceived restoration, while the static group improved vitality and reduced fatigue. Males showed more physiological improvements, whereas females excelled in psychological restoration across all activities.SignificanceConducted in the ecologically rich Panda Valley of Shaanxi Province -a core area of the Giant Panda National Park-this study provides real- world evidence that national parks serve as effective therapeutic landscapes. It offers scientific justification for integrating nature-based therapies into public health strategies and enhancing the health value of national parks.ConclusionForest bathing activities within national parks can serve as a powerful natural therapy for promoting older adult health, tailored by activity type and gender.